Phylogenetic study of living fossil Psilotum nudum L. from Himalayan range of Pakistan using DNA barcodes - Khan, Bushra; Muhammad, Khushi; Hamayun, Zainab; Ur Rehman, Shafee; Majid, Abdul; Que, Youxiong; Nadeem, Muhammad Shahid; Kaleem, Imdad (Bangladesh Journal of Botany, 2019)
The genus Psilotum belongs to Psilotaceae family, with about 133 to 189 species having outstanding social, economic and medically important relict plants. However, being living fossil plant, many hurdles come in way while trying to discern its phylogenetics reconstruction. The partial conserve nucleotide sequences of rbcLa, trnA, trnV, matK, ITS, ycF3 and rpoB genes were used to select the best suitable barcodes in Psilotum nudum L. The amplified fragments were subjected to Sanger sequencing and then Maximum likelihood, Maximum Parsimony and Neighbor Joining trees were generated using bioinformatics software. i.e., MUSCLE, BioEdit and Mega-7. Current population showed the best match between P. complanatum (KY099851.1), population reported from New Zealand and P. nudum (F384430.1) with identity value 100 and 99% having E-value 0.0 and 0.0 by rbcLa and trnA barcode region, respectively. The findings showed that P. nudum L. sequences are ever first reported from the Himalaya regions of Pakistan and could be utilized for further comparison among different populations of this relict plant species across the globe.